2001
DOI: 10.1021/jf010425k
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Aromatic Compounds from Leaves and Stems of Vanilla fragrans

Abstract: Alcoholic extracts of leaves and stems of Vanilla fragrans were fractionated with ethyl acetate and aqueous butanol. All three fractions of ethyl acetate, butanol, and water were screened for toxic bioactivity against mosquito larvae. The results of these experiments showed that the fractions from the ethyl acetate and butanol phases were both active in the bioassay. Bioactivity of the ethyl acetate fraction was found to be much greater than that from the butanol fraction in mosquito larvae toxicity. The water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 10 publications
5
29
0
1
Order By: Relevance
“…The highest concentration was also found to kill eighty percent of the population within 36 hours and likewise, the lowest concentration killed eighty percent of the population. The high mortality rate of the leaf extract at both high and low concentrations is in line with the findings of earlier researchers that most plant extracts showed high larvicidal potential against mosquitoes at relatively high and low concentration (Sharma & Saxena 1994;Sun et al, 2001;Anyaele et al, 2002). Though some larvae survived and eventually became adult, however, they did not live long as adult's emerging from untreated larvae (control).…”
Section: Discussionsupporting
confidence: 89%
“…The highest concentration was also found to kill eighty percent of the population within 36 hours and likewise, the lowest concentration killed eighty percent of the population. The high mortality rate of the leaf extract at both high and low concentrations is in line with the findings of earlier researchers that most plant extracts showed high larvicidal potential against mosquitoes at relatively high and low concentration (Sharma & Saxena 1994;Sun et al, 2001;Anyaele et al, 2002). Though some larvae survived and eventually became adult, however, they did not live long as adult's emerging from untreated larvae (control).…”
Section: Discussionsupporting
confidence: 89%
“…As well as the larvicidal activity of flavonoids was also proved [43,44]. Overall, this research demonstrated larvicidal activity of sixteen extracts obtained from flowers, fruits, stems + leaves and roots of S. arenaria against the mosquito C. pipiens.…”
Section: Discussionsupporting
confidence: 55%
“…Plant as potential larvicides is considered as viable and preferred alternative in the control of the mosquito species at the community level. A large number of plant extracts have been reported to have mosquitocidal or repellent activities against mosquito vectors, but few plant products have shown practical utility for mosquito control [27] . In the present study the apigenin extracted with ethyl alcohol from Jatropha gossypifolia leaf has potent larvicidal activity of Culex quinquefasciatus mosquitoes.…”
Section: Resultsmentioning
confidence: 99%